2016
DOI: 10.1111/jir.12295
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of the physical and psychosocial correlates of Special Olympics participation among individuals with intellectual disability

Abstract: This review highlights the need for a continued critical focus on SO programme evaluation research with more rigorous and replicable methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 97 publications
(249 reference statements)
2
33
0
Order By: Relevance
“…The sample receiving the present intervention had similar characteristics to those reported in other studies with regards to sex, fat mass, fat free mass, and total water mass. The other studies involved participants with the same characteristics as stated in their reviews [52].…”
Section: Discussionmentioning
confidence: 99%
“…The sample receiving the present intervention had similar characteristics to those reported in other studies with regards to sex, fat mass, fat free mass, and total water mass. The other studies involved participants with the same characteristics as stated in their reviews [52].…”
Section: Discussionmentioning
confidence: 99%
“…The studies by Barnet et al (2016b) and Dunphy and Hens (2018) should be highlighted because they considered both physical condition and psychosocial factors in their interventions. Various studies have shown that improvement in physical condition are often accompanied by an improvement in psychosocial aspects and vice versa [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in disability sports can expand athletes' social networks, develop social relationships, facilitate learning and improve their physical and psychological health (McConkey 2016;SPSC 2016;Tint, Thomson & Weiss 2017). According to Liu (2009: 329), Participation [in disability sports] can provide the context within which people exceed the expectations associated with their disability through demonstration of physical skills or fitness, so emphasizing an alternative, more positive, picture of the body and self.…”
Section: Previous Research Ambiguous Binary Meanings On Disability Spmentioning
confidence: 99%